A Dynamic Thermal Camouflage Metadevice with Microwave Scattering Reduction. Issue 22 (5th June 2022) - Yuan, Liming; Huang, Cheng; Liao, Jianming; Ji, Chen; Huang, Jingkai; Wang, Yuetang; Luo, Xiangang
Abstract: With rapid development of radar and infrared (IR) surveillance technologies, the need for microwave‐IR compatible camouflage is now more than ever. Here, a novel multispectral metadevice is proposed to simultaneously achieve microwave scattering reduction, dynamic IR camouflage, and low IR reflection. This metadevice is constructed by the coding thermoelectric elements with the properly designed phase arrangement, and the incident microwave energy can be redirected to the nonthreatening directions for specular reflection reduction. The dynamic IR camouflage with low IR reflection is realized by using the thermoelectric cooling and heating effect and high‐IR‐absorptivity surface. The above three functionalities are demonstrated by experimental measurement. The 10 dB scattering reduction can be realized at the microwave band of 10–16.1 GHz. In the IR region, the designed metadevice can not only dynamically modulate the surface temperature for matching different background temperatures, but also realize the pixel temperature control for adapting to a spatially varying thermal background. In addition, it reflects almost no surrounding thermal signals compared with the traditional low‐emissivity IR stealth material. This study paves an effective way to achieve microwave‐IR compatible camouflage, which may inspire the future researches and applications in multispectral camouflage and stealth fields. Abstract : This report presents an innovative thermoelectric metadevice, which can not only reduce the microwave specular scattering by beam‐splitting effect, but also achieve dynamic IR camouflage by the modulation of surface temperature along with minimizing the reflection of surrounding thermal signals. The multifunctional metadevice paves an effective way to researches of multispectral camouflage and stealth fields.